2005
DOI: 10.1111/j.1467-9817.2005.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in RAN and reading: a response timing analysis

Abstract: Thirty 8-11-year-old children were administered tests of rapid naming (RAN letters and digits) and reading-related skills. Consistent with the hypothesis that RAN predicts reading because it assesses the ability to establish arbitrary mappings between visual symbols and verbal labels, RAN accounted for independent variance in exception word reading when phonological skills were controlled. Response timing analysis of different components of RAN digits and letters revealed that neither average item duration nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
88
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 32 publications
6
88
1
4
Order By: Relevance
“…A set of behavioral studies viewed visual naming impairments as symptoms of a deficit within the phonological processing system, in particular, the naming delay occurs at the level of phonological encoding -the on-line process of activating/accessing phonological information during spoken word production -and/or in the formation of (specified) phonological representations (discrete naming: Faust and Sharfstein-Friedman (2003), Nation et al (2001), Swan and Goswami (1997a) and Truman and Hennessey (2006); serial naming: Clarke et al (2005) and Pennington et al (2001)). In support of this view, naming performance by dyslexic children is more sensitive to lexical variables that affect the complexity of phonological encoding, such as the word length, compared to controls (Nation et al, 2001;Swan and Goswami, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…A set of behavioral studies viewed visual naming impairments as symptoms of a deficit within the phonological processing system, in particular, the naming delay occurs at the level of phonological encoding -the on-line process of activating/accessing phonological information during spoken word production -and/or in the formation of (specified) phonological representations (discrete naming: Faust and Sharfstein-Friedman (2003), Nation et al (2001), Swan and Goswami (1997a) and Truman and Hennessey (2006); serial naming: Clarke et al (2005) and Pennington et al (2001)). In support of this view, naming performance by dyslexic children is more sensitive to lexical variables that affect the complexity of phonological encoding, such as the word length, compared to controls (Nation et al, 2001;Swan and Goswami, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Pause time is interpreted as a measure of retrieval time from phonological memory. However, Clarke, Hulme, and Snowling (2005) failed to replicate this result when the reading measure used was exception word reading. Clarke et al noted that better readers paused more strategically (i.e., more often at the ends of lines) than poorer readers, and they suggested that differences in RAN may in part reflect differences in strategic control that result from differences in reading practice and experience.…”
mentioning
confidence: 98%
“…Subjacente ao desenvolvimento de cada componente da leitura (precisão, fluência e compreensão) está um conjunto de variáveis cognitivas e metalinguísticas, sendo algumas delas o conhecimento do nome das letras, a memória de trabalho, a consciência fonológica (habilidade de perceber e manipular os sons das palavras faladas; Bryant & Bradley, 1987), a consciência morfológica (consciência da estrutura morfológica das palavras e habilidade de refletir sobre e manipular essa estrutura; Carlisle, 1995), o vocabulário e a habilidade de fazer inferências (Snowling & Hulme, 2005). Essas variáveis não se relacionam igualmente com todos os componentes da leitura.…”
unclassified
“…No entanto, outras tarefas também podem ser encontradas na literatura. Essas outras tarefas, apesar de muito semelhantes às de Denckla e Rudel, diferem dessas na quantidade de itens em uma mesma tarefa (15 itens em Landerl & Willbuger, 2010;25 itens em Zhou et al, 2014;36 itens em Logan, Schatschneidere, & Wagner, 2011;40 itens em Shapiro, Carroll, & Solity, 2013;48 em Clarke, Hulme, & Snowling, 2005) e/ou na quantidade de estímulos diferentes em cada tarefa (seis itens diferentes em Pauly, Linkersdörfer, & Lindberg, 2011, e Logan et al, 2011; 10 a 25 itens diferentes em Clarke et al, 2005; 20 itens em Cobbold, Passenger, & Terrel, 2003). Embora essas variações pudessem, a princípio, afetar a relação entre a nomeação seriada rápida e a leitura, a meta-análise realizada por Araújo et al (2015) revelou que nenhum desses aspectos (variação no tamanho da tarefa ou na quantidade de itens diferentes incluídos) teve um impacto significativo na magnitude da correlação entre a nomeação seriada rápida e a leitura.…”
unclassified